Digital Transformation of Acquisition Fee Of Right On Land and Building Collection in Accelerating Property Registration Services at Jakarta Province - Annissa Faya Nurleni; Roy Valiant Salomo (Jurnal Teknologi Informasi dan Pendidikan, 2023)
Technological developments have influenced how humans work and interaction. Digital transformation is a holistic effort to revise core government processes and services. Digital transformation is a change from an analog system to a digital system by reviewing policies, current processes, and user needs. Ultimately it will result in a revision of a policy, resulting in the creation of a new digital service. This research was prepared using qualitative methods with descriptive research type. This research aims to analyze the dimensions of the digital transformation of BPHTB collection acceleration of property registration services in DKI Jakarta Province as stated in DKI Jakarta Governor Regulation Number 34 of 2022. The digital transformation of BPHTB Elections is a form of digital transformation of services tax area that can simplify the service process tax areas and speed up the service process registration property. Change culture in the research workflow previously officer done manually by officers after There is policy digital transformation of E-BPHTB reporting is done by the system or in a way electronics. Through the e-BPHTB service, taxpayers can download the BPHTB SSPD online and just in time without the need to come to the office tax area. Digital transformation is influenced by external factors and internal factors so that it can change the objects and processes of a service through the use of digital technology which can produce a new service aimed at improving service delivery and increasing accountability.